Kenyan Plasmodium falciparum Field Isolates: Correlation between Pyrimethamine and Chlorcycloguanil Activity In Vitro and Point Mutations in the Dihydrofolate Reductase Domain - Nzila-Mounda, A. (American Society for Microbiology, 1998)
Sixty-nine Kenyan Plasmodium falciparum field isolates were tested in vitro against pyrimethamine (PM), chlorcycloguanil (CCG), sulfadoxine (SD), and dapsone (DDS), and their dihydrofolate reductase (DHFR) genotypes were determined. The in vitro data show that CCG is more potent than PM and that DDS is more potent than SD. DHFR genotype is correlated with PM and CCG drug response. Isolates can be classified into three distinct groups based on their 50% inhibitory concentrations (IC(50)s) for PM and CCG (P < 0.01) and their DHFR genotypes. The first group consists of wild-type isolates with mean PM and CCG IC(50)s of 3.71 ± 6.94 and 0.24 ± 0.21 nM, respectively. The second group includes parasites which all have mutations at codon 108 alone or also at codons 51 or 59 and represents one homogeneous group for which 25- and 6-fold increases in PM and CCG IC(50)s, respectively, are observed. Parasites with mutations at codons 108, 51, and 59 (triple mutants) form a third distinct group for which nine- and eightfold increases in IC(50)s, respectively, of PM and CCG compared to the second group are observed. Surprisingly, there is a significant decrease (P < 0.01) of SD and DDS susceptibility in these triple mutants. Our data show that more than 92% of Kenyan field isolates have undergone at least one point mutation associated with a decrease in PM activity. These findings are of great concern because they may indicate imminent PM-SD failure, and there is no affordable antimalarial drug to replace PM-SD (Fansidar).